1996
DOI: 10.1111/j.1365-2958.1996.tb02626.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and functional characterization of PecS, a regulator of virulence‐factor synthesis in Erwinia chrysanthemi

Abstract: The Erwinia chrysanthemi pecS gene encodes a repressor that negatively regulates the expression of virulence factors such as pectinases or cellulases. The cloned pecS gene was overexpressed using a phage T7 system. The purification of PecS involved DEAE-anion exchange and TSK-heparin columns and delivered the PecS protein that was purified to homogeneity. The purified repressor displayed an 18 kDa apparent molecular mass and an isoelectric point near to neutrality (pl = 6.5). Gel-filtration experiments reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 40 publications
4
75
0
Order By: Relevance
“…The expression of kdgM is 3-fold repressed with the presence of glucose in the medium or in a crp mutant, indicating that kdgM is submitted to the catabolite repression via the CRP activator. A 7-fold increase in kdgM expression was observed in a pecS mutant (40,20). This regulation by PecS seems to occur essentially during the late exponential or early stationary phase of growth (data not shown).…”
Section: Kdgm Is a Major Outer Membrane Protein Of Pectinolyticmentioning
confidence: 89%
See 1 more Smart Citation
“…The expression of kdgM is 3-fold repressed with the presence of glucose in the medium or in a crp mutant, indicating that kdgM is submitted to the catabolite repression via the CRP activator. A 7-fold increase in kdgM expression was observed in a pecS mutant (40,20). This regulation by PecS seems to occur essentially during the late exponential or early stationary phase of growth (data not shown).…”
Section: Kdgm Is a Major Outer Membrane Protein Of Pectinolyticmentioning
confidence: 89%
“…Band shift assays were performed with the KdgR-, CRP-, and PecS-purified proteins (32,33,40). The labeled DNA fragment (50,000 cpm) and 5-100 nM of the purified regulator were incubated for 30 min at 30°C in 20 l of binding buffer, and the reaction mixtures were submitted to electrophoresis on a 4% non-denaturing polyacrylamide gel, as described previously (33,40).…”
Section: Methodsmentioning
confidence: 99%
“…A similar inverted repeat lies between the promoter and start codon of SlyA (see Ludwig et al, 1995). In contrast, the Hpr-binding sites appear to be a somewhat shorter and imperfect inverted repeat (Kallio et al, 1991), whilst the PecS-binding sites appear to be much longer (Praillet et al, 1996) …”
Section: Cinr Binds To Sequences Between Cinr and Cinbmentioning
confidence: 99%
“…In E. chrysanthemi, it has been demonstrated that the full expression of the pectin catabolism genes requires the presence of the cAMP-CRP complex Reverchon et al, 1997) and that the KdgR repressor essentially mediates the induction of these catabolic pathway genes by pectic compounds (Reverchon et al, 1991;Nasser et al, 1994). In addition to kdgR, two other loci involved in negative regulation of the pectinase gene expression, pecS-pecM and pecT, were also characterized in E. chrysanthemi, but the signal to which they respond still remains unknown (Praillet et al, 1996;Reverchon et al, 1994;Surgey et al, 1996;Castillo and Reverchon, 1997).…”
Section: Introductionmentioning
confidence: 99%